New drugs for the treatment of hyperlipidemia in statin-intolerant patients - review - Płonka, Wojciech; Pelc, Marcin; Sitarek, Gracjan; Żerek, Marta; Bułatowicz, Monika; Liber, Joanna; Banach, Krzysztof; Chruścicki, Damian; Pławiak, Aleksandra (Journal of Education, Health and Sport, 2024)
Introduction Cardiovascular diseases are the most numerous group of diseases prevalent in the world. They are a challenge for many health systems, in terms of keeping life comfortable and also economics. The cause of selected disease entities is too much cholesterol in the blood. The most popular treatment for hypercholesterolemia is based on statins. Many patients are affected by intolerance to these drugs, so an important issue is the discovery and improvement of alternatives to statins. Purpose of work The purpose of this review is to collect literature data on the latest treatments for hypercholesterolemia with drugs other than statins and ezetimibe. Materials and methods Materials are from a review of recent literature available in PubMed. To search for articles, we used keywords such as: bempedoic acid, non-statin therapy, cardiovascular risk, inclisiran, alirocumab, cardiovascular disease, dyslipidemia, evolocumab. Summary Treatment of hypercholesterolemia with statins remains the most popular management strategy. Intolerance to treatment with these drugs creates serious clinical problems for patients. Recently, we could see the emergence of new drugs as alternatives to statins. As the results show, the new drugs can effectively replace statins in the hypolipemic treatment especially of patients who cannot be treated with them.